Research progress of immunoassay technology in mycotoxin detection - LIU Yingda; LIU Haiyuan; SU Na; MING Liang; HE Jing; Tuyatsetseg Jambal; B.Maizul; Jirimutu; YI Li (Zhongguo shipin weisheng zazhi, 2023)
Mycotoxins are secondary metabolites produced by fungi under suitable conditions. Mycotoxins not only endanger humans and animals， but also cause immeasurable damage to the agricultural economy. The common mycotoxin detection methods mainly feature large-scale instrument detection， which requires professional laboratory personnel and takes a long time. Emerging immunoassay technologies have the advantages of simple operation， speed， low cost， minimal interference， and the ability to process several samples simultaneously. This paper reviews the development of immunogens and antibodies in several common immunoassay techniques in the recent years and systematically compares the advantages and disadvantages of various immunoassay techniques. This review provides a novel idea for the development of immunoassay technology in mycotoxin detection.